(Invited) Study on the Role of Thermal Stress on Prismatic Slip of Dislocations in 4H-SiC Crystals Grown by PVT Method. (23rd August 2016) - Guo, Jianqiu; Yang, Yu; Goue, Ouloide Yannick; Raghothamachar, Balaji; Dudley, Michael
Abstract : Basal plane slip is most frequently observed deformation mechanism in 4H type silicon carbon (4H-SiC) single crystals grown by physical vapor transport (PVT) method. It has recently been reported, however, dislocations in such crystals can also glide in the prismatic slip systems. In our study, we have observed non-uniform distributions of three sets of prismatic dislocations in a commercial 4H-SiC substrate wafer. The non-uniformity is likely a result of the distribution of resolved shear stress on each prismatic slip system caused by the radial thermal gradients in the growing crystal boule. A radial thermal model during PVT growth has been developed to estimate the thermal stress across the entire area of the crystal boule. The model makes an excellent agreement with the actual observation, confirming that radial thermal gradients play a key role in activating prismatic slip in 4H-SiC during bulk growth.